Gender differences among Black adolescents in foster care: The relationship between relational permanence and psychological well-being. Issue 4 (7th August 2020) - Williams-Butler, Abigail; Gale, Adrian; Dorsey, Marquitta
ABSTRACT: Black adolescents in the foster care system are at risk for a wide variety of negative outcomes. However, little is known about the role of multilevel promotive factors, particularly relational permanence, in promoting resilience in regards to race and gender for Black adolescents in foster care. This longitudinal study examines whether gender impacts the association between multilevel promotive factors and psychological well-being among Black adolescents in foster care. Participants were 489 Black adolescents who completed the Illinois Department of Children and Family Services Child and Adolescent Needs and Strengths assessment between 2007 and 2012. It was hypothesized that promotive factors would play a different role for Black boys and girls. Findings indicate that relational permanence was positively associated with psychological well-being for Black boys, but not for Black girls. Additionally, maltreatment type and number of placements also significantly predicted relational permanence at Time 2 for boys, but not girls. Taken together, these findings suggest that more attention needs to focus on promotive factors that predict positive outcomes for Black girls in the foster care system. Implications for practice and policy related to the gendered needs of Black adolescents in foster care are discussed.